Energy Harvesting for Sensors of Structural Integrity in Wind Power Stations - Christopher Behnke; Werner Karl Schomburg (Proceedings, 2017)
The structural integrity of the rotors of wind power stations can be monitored by a variety of sensors. However, the power supply of the employed sensors should not be connected by cable because lightning strikes are provoked that way. Therefore, energy harvesting systems are an interesting alternative. Three concepts for electrical power generation by harvesting the energy from the movements inside of rotor blades of wind power stations are described and compared to each other. Inside of such rotor blades, large vibration amplitudes of up to 15 cm are available but only at a frequency of a few Hertz. The available space is on the order of 20 × 20 × 40 cm3. A beam equipped with piezos and repelling magnets turned out being the most promising solution.